Preparation method and application of high-purity nano tourmaline powder

Through mechanical grinding and washing technology, high-purity nano-tourmaline powder is prepared, which solves the problems of existing tourmaline powder with large particles and many impurities, and significantly improves the performance and quality of the product.

CN119349591APending Publication Date: 2025-01-24SUZHOU ROUTAO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411535796.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing tourmaline powder particles are coarse, have a large number of impurities, and have a high impurity content. Due to its large surface energy, it is easy to agglomerate, resulting in poor performance.

Method used

Nanoscale tourmaline powder is prepared through mechanical grinding, and based on this, washing and impurity removal are performed to reduce the impurity content and improve purity. The specific steps include wet ball milling, pickling, primary sand grinding, organic solvent washing and secondary sand grinding, and finally high-purity nano tourmaline powder is obtained.

Benefits of technology

The particle size of the electrical stone powder is reduced, the concentration of negative ions releases the concentration, the product quality and performance are significantly improved, the cost is low, and it is easy to industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349591A_ABST
    Figure CN119349591A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of high-purity nano tourmaline powder, and belongs to the technical field of functional material preparation. The preparation method of the high-purity nano tourmaline powder comprises the following steps: S1, putting tourmaline powder of which the purity is not less than 98% into ball milling equipment for wet ball milling; carrying out ball milling until the average particle size does not exceed 500nm, taking out, and carrying out acid pickling, so as to obtain tourmaline slurry; s2, sieving the tourmaline slurry, drying screen underflow, and putting the dried screen underflow into a sand mill for primary sand milling; sanding until the average particle size does not exceed 200nm, and adding an organic solvent for washing to obtain a washing solution; s3, sieving the washing liquid, drying screen underflow, and performing secondary sanding on the screen underflow in the sand mill; and (3) adding the nano tourmaline powder into a grinding machine, grinding until the average particle size does not exceed 50nm, centrifuging to remove supernate to obtain a precipitate, and finally drying to obtain high-purity nano tourmaline powder. Nanoscale tourmaline powder is prepared through mechanical grinding, washing and impurity removal are carried out on the basis, the impurity content in the tourmaline powder is reduced, and the purity of the tourmaline powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of functional material preparation, in particular to a preparation method and application of high-purity nano tourmaline powder. Background Art

[0002] Tourmaline, whose mineralogical name is tourmaline, is a borosilicate crystal containing chemical elements such as aluminum, iron, magnesium, sodium, lithium, and potassium. Tourmaline has piezoelectricity and thermoelectricity, and can form a persistent electric field on the surface, thereby ionizing water molecules and oxygen molecules in its environment and generating negative ions. Negative ions have a positive impact on human health, promoting blood circulation, improving respiratory function, and regulating blood pressure. In addition, negative ions can also precipitate dust and harmful substances in the air, reduce PM2.5, thereby purifying the environment and indirectly improving human health. Its concentration is often used as one of the indicators for evaluating air quality. In addition to generating negative ions, the electric field formed on the surface of tourmaline can also reduce the recombination of electrons and holes, so it has a certain adsorption capacity and has good application prospects in photocatalysis and water treatment. In addition, tourmaline also has far-infrared radiation ability and a certain antibacterial ability. Thanks to the above excellent functions, tourmaline is widely used in environmental protection, electronics, daily chemicals, textile ceramics, building materials and other industries.

[0003] Theoretically, the powder prepared by crushing natural tourmaline (hereinafter referred to as tourmaline powder) has more micro-electric fields, and the piezoelectric and thermoelectric effects can be further improved. However, at present, tourmaline powder has not shown better performance because the prepared tourmaline powder has coarse particles, many types of impurities, high impurity content, and is easy to agglomerate due to its large surface energy.

[0004] In order to solve the above problems in the prior art, the present invention is provided. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a method for preparing high-purity nano tourmaline powder and its application, wherein the nano-level tourmaline powder is prepared by mechanical grinding, and then washed and impurities are removed on this basis to reduce the impurity content in the tourmaline powder and improve its purity.

[0006] The first aspect of the present invention relates to a method for preparing high-purity nano tourmaline powder, comprising the following steps:

[0007] S1, putting tourmaline powder with a purity of not less than 98% into a ball mill for wet ball milling, using alumina balls as ball milling media and ultrapure water as ball milling medium liquid; after ball milling until the average particle size does not exceed 500nm, taking out and adding an acidic substance for pickling to obtain tourmaline slurry;

[0008] S2, sieving the tourmaline slurry, drying the sieved material, and putting it into a sand mill for a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid; after sand milling until the average particle size does not exceed 200 nm, adding an organic solvent for washing to obtain a washing liquid;

[0009] S3, sieving the washing liquid, drying the sieved material and putting it into a sand mill for secondary sand grinding, using alumina balls as sand grinding medium and ultrapure water as sand grinding medium liquid; after sand grinding to an average particle size not exceeding 50nm, centrifugally removing the supernatant to obtain a precipitate, and finally drying to obtain high-purity nano tourmaline powder.

[0010] For some specific implementation schemes, in step S1, the weight ratio of tourmaline powder, alumina balls and ultrapure water is 1:1 to 3:1 to 3. For example, the weight ratio can be 1:1:1, 1:1:2, 1:1:3, 1:2:1, 1:2:2, 1:2:3, 1:3:1, 1:3:2, 1:3:3, etc.

[0011] For some specific implementation schemes, in step S1, the ball milling speed is 200-300 rpm, and the time is 6-12 h; for example, the ball milling speed is 200 rpm, 220 rpm, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, etc., and the ball milling time is 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, etc.

[0012] For some specific implementation schemes, in step S1, the acidic substance can be a solid acid or a liquid acid, and the weight ratio of the acidic substance to the tourmaline powder is 0.05 to 0.1:1; for example, the weight ratio can be 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, etc.

[0013] Preferably, the acidic substance is at least one of nitric acid, acetic acid, citric acid and boric acid.

[0014] For some specific implementation schemes, in step S2, the sanding time is 6 to 12 hours; for example, the sanding time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0015] For some specific implementation schemes, in step S2, the amount of organic solvent added is 1% to 5% of the weight of the tourmaline powder; for example, the amount added is 1%, 2%, 3%, 4%, 5%, etc.; preferably, the organic solvent is at least one of dimethyl sulfoxide, carbon tetrachloride, and ethanol; the ethanol can be anhydrous ethanol.

[0016] For some specific implementation schemes, in step S3, the secondary sanding time is 6 to 12 hours; for example, the sanding time can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc.

[0017] The second aspect of the present invention relates to a tourmaline, which is obtained by placing the above-mentioned high-purity nano-tourmaline powder in a mold, isostatically pressing it and then sintering it.

[0018] For some specific implementation schemes, the isostatic pressing pressure is 100-300 MPa, the sintering temperature is 800-1600°C, the sintering time is 30-60 min, and the heating rate is 10-20°C / min; for example, the isostatic pressing pressure is 100 MPa, 120 MPa, 150 MPa, 200 MPa, 210 MPa, 240 MPa, 260 MPa, 290 MPa, 300 MPa, etc., and the sintering temperature is 800°C, 900°C, 100 0℃, 1100℃, 1200℃, 1300℃, 1400℃, 1500℃, 1600℃, etc. The sintering time is 30min, 40min, 50min, 60min, etc. The heating rate is 10℃ / min, 11℃ / min, 12℃ / min, 13℃ / min, 14℃ / min, 15℃ / min, 16℃ / min, 17℃ / min, 18℃ / min, 19℃ / min, 20℃ / min, etc.

[0019] Compared with the prior art, the present invention has the following technical effects:

[0020] 1) Mechanical grinding is used to grind tourmaline. In addition to the grinding medium liquid, no complex chemical additives are required to avoid the introduction of additional impurities, and no harsh reaction conditions are required. Therefore, the cost is relatively low, and it is easy to achieve industrial production, which can meet the needs of large-scale preparation of high-purity nano-level tourmaline powder materials;

[0021] 2) The mechanical grinding method of first ball milling and then two sand millings is adopted to improve the grinding efficiency, optimize the particle size and particle size distribution, and help improve the electrical properties of tourmaline; acidic substances are added for pickling after ball milling and before the first sand milling to remove inorganic impurities, thereby improving the purity, having high impurity removal efficiency and having little effect on the particle size and particle size; organic solvents are added for washing before the second sand milling, which can more effectively remove organic impurities under the condition of smaller particle size and larger specific surface area, further improving the purity and promoting the dispersion of fine particles, thereby enhancing the stability of the particles; while optimizing the particle size and particle size distribution and improving the purity of tourmaline powder, the product quality is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the high-purity nano-tourmaline powder prepared in Example 1. DETAILED DESCRIPTION

[0023] The present invention is described in detail below in conjunction with the accompanying drawings. The experimental methods without specific conditions in the embodiments are carried out according to conventional methods and conditions.

[0024] Test Method

[0025] 1. Microstructure

[0026] Test method: Refer to "EN 623-3:1993 Advanced technical ceramics-Monolithic ceramics General and textural properties-Part 3: Determination of grain sizeand size distribution (characterized by the Linear Intercept Method)" and use Zeiss scanning electron microscope to take morphological photos.

[0027] 2. Static average negative ion release solubility, average particle size, hardness, relative density, refractive index

[0028] The test method for static average negative ion release solubility refers to GB / T 18809-2016 "Measurement method for air negative ion concentration";

[0029] The test method of average particle size refers to GB / T 20000.1-2004 "Determination of physical properties of particles Part 1: Particle size analysis";

[0030] The test methods for hardness, relative density and refractive index refer to GB / T 16553-2017 "Identification of Jewelry and Jade".

[0031] Example 1

[0032] The process of preparing high-purity tourmaline in this embodiment is as follows.

[0033] S1, adding 98% pure tourmaline powder, alumina balls and ultrapure water in a weight ratio of 1:2:2 into a ball mill, and milling at a speed of 300 rpm for 12 hours; taking out, and after testing, the average particle size of the tourmaline powder reaches 500 nm; adding nitric acid at 10% of the weight of the tourmaline powder for pickling to obtain tourmaline slurry;

[0034] S2, sieving the tourmaline slurry, drying the sieve material, and putting it into a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid, and performing sand milling once; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 200nm, adding anhydrous ethanol according to 5% of the weight of the tourmaline powder for washing, and obtaining a washing liquid;

[0035] S3, sieving the washing liquid, drying the sieve, putting the sieve under the sieve into a sand mill, using alumina balls as sand milling medium and ultrapure water as sand milling medium liquid, and performing secondary sand milling; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 50nm, centrifuging to remove the supernatant, obtaining a precipitate, and finally drying to obtain a high-purity nano tourmaline powder;

[0036] S4, placing high-purity nano tourmaline powder into a mold and isostatically pressing it at a pressure of 300 MPa, sintering it in air at a sintering temperature of 1600°C, a sintering time of 60 minutes, and a heating rate of 10°C / min, to finally produce high-purity tourmaline.

[0037] Example 2

[0038] The process of preparing high-purity tourmaline in this embodiment is as follows.

[0039] S1, adding tourmaline powder with a purity of 98%, alumina balls and ultrapure water in a weight ratio of 1:2:1 into a ball mill, and milling at a speed of 300 rpm for 12 hours; taking out, and after testing, the average particle size of the tourmaline powder reaches 500 nm; adding nitric acid at 5% of the weight of the tourmaline powder for pickling to obtain tourmaline slurry;

[0040] S2, sieving the tourmaline slurry, drying the sieve material, and putting it into a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid, and performing sand milling once; sand milling for 10 hours, after testing, the average particle size of the tourmaline powder reaches 200nm, adding anhydrous ethanol according to 5% of the weight of the tourmaline powder for washing, and obtaining a washing liquid;

[0041] S3, sieving the washing liquid, drying the sieve, putting it into a sand mill, using alumina balls as sand milling medium, and ultrapure water as sand milling medium liquid, and performing secondary sand milling; sand milling for 12 hours, after testing, the average particle size of the tourmaline powder reaches 50nm, centrifuging to remove the supernatant, obtaining a precipitate, and finally drying to obtain high-purity nano tourmaline powder, the scanning electron microscope image of which is as shown in Figure 1 As shown, the particle size distribution is uniform;

[0042] S4, placing high-purity nano tourmaline powder into a mold and isostatically pressing it at a pressure of 300 MPa, sintering it in air at a sintering temperature of 1600°C, a sintering time of 60 minutes, and a heating rate of 10°C / min, to finally produce high-purity tourmaline.

[0043] Example 3

[0044] The process of preparing high-purity tourmaline in this embodiment is as follows.

[0045] S1, adding 98% pure tourmaline powder, alumina balls and ultrapure water into a ball mill at a weight ratio of 1:2:3, and ball milling at a speed of 300 rpm for 12 hours; taking out, and after testing, the average particle size of the tourmaline powder reaches 500 nm; adding nitric acid at 5% of the weight of the tourmaline powder for pickling to obtain tourmaline slurry;

[0046] S2, sieving the tourmaline slurry, drying the sieve material, and putting it into a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid, and performing sand milling once; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 200nm, adding anhydrous ethanol according to 5% of the weight of the tourmaline powder for washing, and obtaining a washing liquid;

[0047] S3, sieving the washing liquid, drying the sieve, putting the sieve under the sieve into a sand mill, using alumina balls as sand milling medium and ultrapure water as sand milling medium liquid, and performing secondary sand milling; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 50nm, centrifuging to remove the supernatant, obtaining a precipitate, and finally drying to obtain a high-purity nano tourmaline powder;

[0048] S4, placing high-purity nano tourmaline powder into a mold and isostatically pressing it at a pressure of 300 MPa, sintering it in air at a sintering temperature of 1600°C, a sintering time of 60 minutes, and a heating rate of 10°C / min, to finally produce high-purity tourmaline.

[0049] Example 4

[0050] The process of preparing high-purity tourmaline in this embodiment is as follows.

[0051] S1, adding tourmaline powder with a purity of 98%, alumina balls and ultrapure water in a weight ratio of 1:2:2 into a ball mill, and milling at a speed of 300 rpm for 12 hours; taking out, and after testing, the average particle size of the tourmaline powder reaches 500 nm; adding acetic acid at 5% of the weight of the tourmaline powder for pickling to obtain tourmaline slurry;

[0052] S2, sieving the tourmaline slurry, drying the sieve material, and putting it into a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid, and performing sand milling once; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 200nm, adding anhydrous ethanol according to 5% of the weight of the tourmaline powder for washing, and obtaining a washing liquid;

[0053] S3, sieving the washing liquid, drying the sieve, putting the sieve under the sieve into a sand mill, using alumina balls as sand milling medium and ultrapure water as sand milling medium liquid, and performing secondary sand milling; sand milling for 6 hours, after testing, the average particle size of the tourmaline powder reaches 50nm, centrifuging to remove the supernatant, obtaining a precipitate, and finally drying to obtain a high-purity nano tourmaline powder;

[0054] S4, placing high-purity nano tourmaline powder into a mold and isostatically pressing it at a pressure of 300 MPa, sintering it in air at a sintering temperature of 1600°C, a sintering time of 60 minutes, and a heating rate of 10°C / min, to finally produce high-purity tourmaline.

[0055] The high-purity nano-tourmaline powder and high-purity tourmaline obtained in Examples 1 to 4 were tested, and the results are shown in Table 1 below.

[0056] Table 1 Test results project Static average anion release concentration (ions / cm³) Average particle size (nm) Tourmaline Hardness Tourmaline relative density (GPa) Tourmaline Refractive Index Example 1 8153 61 7.3 3.15 1.621 Example 2 9813 50 7.5 3.26 1.665 Example 3 8361 58 7.3 3.18 1.636 Example 4 8497 54 7.4 3.21 1.657 Raw Tourmaline Powder 4500 17000 7.0 3.10 1.611

[0057] It can be found that the mechanical grinding process of first ball milling and then twice ball milling in Examples 1 to 4 combined with acid washing and organic solvent washing, the average particle size of the tourmaline powder obtained is greatly reduced compared with the original tourmaline powder, and the negative ion release concentration is significantly improved; and the tourmaline prepared is also improved in hardness, relative density and refractive index compared with the original tourmaline, and the negative ion release concentration is significantly improved.

[0058] It should be emphasized that the above are only preferred embodiments of the present invention and do not impose any form of limitation on the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing high-purity nano tourmaline powder, characterized in that: The following steps are involved: S1, putting tourmaline powder with a purity of not less than 98% into a ball mill for wet ball milling, using alumina balls as ball milling media and ultrapure water as ball milling medium liquid; after ball milling until the average particle size does not exceed 500nm, taking out and adding an acidic substance for pickling to obtain tourmaline slurry; S2, sieving the tourmaline slurry, drying the sieved material, and putting it into a sand mill for a sand mill, using alumina balls as sand milling media and ultrapure water as sand milling medium liquid; after sand milling until the average particle size does not exceed 200 nm, adding an organic solvent for washing to obtain a washing liquid; S3, sieving the washing liquid, drying the sieved material and putting it into a sand mill for secondary sand grinding, using alumina balls as sand grinding medium and ultrapure water as sand grinding medium liquid; after sand grinding to an average particle size not exceeding 50nm, centrifugally removing the supernatant to obtain a precipitate, and finally drying to obtain high-purity nano tourmaline powder.

2. The preparation method according to claim 1, characterized in that: In the step S1, the weight ratio of tourmaline powder, alumina balls and ultrapure water is 1:1-3:1-3.

3. The preparation method according to claim 2, characterized in that: In the step S1, the ball milling speed is 200-300 rpm and the time is 6-12 hours.

4. The preparation method according to claim 3, characterized in that: In the step S1, the weight ratio of the acidic substance to the tourmaline powder is 0.05-0.1:1; the acidic substance is at least one of nitric acid, acetic acid, citric acid and boric acid.

5. The preparation method according to claim 4, characterized in that: In the step S2, the sand grinding time is 6 to 12 hours.

6. The preparation method according to claim 5, characterized in that: In the step S2, the amount of organic solvent added is 1% to 5% of the weight of the tourmaline powder.

7. The preparation method according to claim 6, characterized in that: In step S2, the organic solvent is at least one of dimethyl sulfoxide, carbon tetrachloride, and ethanol.

8. The preparation method according to claim 7, characterized in that: In step S3, the secondary sand grinding time is 6 to 12 hours.

9. A tourmaline, characterized in that: The high-purity nano tourmaline powder according to any one of claims 1 to 8 is placed in a mold, isostatically pressed and then sintered.

10. The tourmaline according to claim 9, characterized in that: The isostatic pressing pressure is 100-300MPa, the sintering temperature is 800-1600°C, the sintering time is 30-60min, and the heating rate is 10-20°C / min.